Strategi Guru Dalam Pembelajaran Al-Qur’an Melalui Metode At-Tartil - Ziadatun Nafisah (CV. Satria Jaya, 2024)
As a Muslim we have a guide in life, namely the holy book of the Qur'an, so this is an obligation for every Muslim to study the Qur'an and practice it in everyday life. Learning the Qur'an is a process that produces changes and the ability to pronounce words, or the letters of the Qur'an starting with the letter